Complementarity in the Rome Statute and national criminal jurisdictions - Kleffner, Jann K. (Oxford : Oxford University Press, 2008)
An in-depth examination of the principle of complementarity in the Rome Statute of the International Criminal Court and the implications of that principle for the suppression of genocide crimes against humanity and war crimes on the domestic level.
Description based on print version record.
Includes bibliographical references and index.
Keywords: International Criminal Court; Rome Statute of the International Criminal Court (1998); Criminal liability (International law); Jurisdiction (International law)